(untitled) (International Journal of Scientific Trends, 2023)
In this article, the specific aspects of the development of mountain and sub-mountain areas , the most important elements of the mountain relief, the meaning of the concept of mountain and mountain system, the hierarchically defined levels of the mountain as a scientific concept and their characteristics, the interpretation of the height limits of the natural-social economic altitude zones, and the legal issues related to the formation of the mountain national policy for the sustainable development of the mountain regions of the country are analyzed.